Alkyl chain length-dependent surface reaction of dodecahydro-N-alkylcarbazoles on Pt model catalysts - Gleichweit, Christoph; Amende, Maximilian; Bauer, Udo; Schernich, Stefan; Höfert, Oliver; Lorenz, Michael Peter Andreas; Zhao, Wei; Müller, Michael; Koch, Marcus; Bachmann, Philipp; Wasserscheid, Peter; Libuda, Jörg; et al. (Journal of Chemical Physics, 2014)
The concept of liquid organic hydrogen carriers (LOHC) holds the potential for large scale chemical storage of hydrogen at ambient conditions. Herein, we compare the dehydrogenation and decomposition of three alkylated carbazole-based LOHCs, dodecahydro-N-ethylcarbazole (H-NEC), dodecahydro-N- propylcarbazole (H-NPC), and dodecahydro-N-butylcarbazole (H -NBC), on Pt(111) and on AlO-supported Pt nanoparticles. We follow the thermal evolution of these systems quantitatively by in situ high-resolution X-ray photoelectron spectroscopy. We show that on Pt(111) the relevant reaction steps are not affected by the different alkyl substituents: for all LOHCs, stepwise dehydrogenation to NEC, NPC, and NBC is followed by cleavage of the C-N bond of the alkyl chain starting at 380-390 K. On Pt/AlO, we discern dealkylation on defect sites already at 350 K, and on ordered, (111)-like facets at 390 K. The dealkylation process at the defects is most pronounced for NEC and least pronounced for NBC. © 2014 AIP Publishing LLC.

Benzoic Acid and Phthalic Acid on Atomically Well-Defined MgO(100) Thin Films: Adsorption, Interface Reaction, and Thin Film Growth - Xu, Tao; Mohr, Susanne; Amende, Maximilian; Laurin, Mathias; Döpper, Tibor; Görling, Andreas; Libuda, Jörg (Journal of Physical Chemistry C, 2015)
To better understand the interaction and the growth of thin films of functionalized organic molecules on oxide surfaces, we have studied the adsorption, reaction, and desorption of benzoic acid (BA) and phthalic acid (PA) on a well-ordered MgO(100) thin film grown on a Ag(100) single crystal surface. We have applied isothermal time-resolved infrared reflection absorption spectroscopy (TR-IRAS) and temperature-programmed IRAS (TP-IRAS) under ultrahigh-vacuum (UHV) conditions. BA is dosed using a supersonic molecular beam (SSMB) source while PA is deposited by physical vapor deposition (PVD). For both molecules we have explored the film growth as a function of temperature, both in the monolayer and in the multilayer regime. We have also investigated structural transitions and desorption by temperature-programmed experiments in the range from 100 to 400 K. In addition, we carried out density-functional (DF) calculations. We find that both molecules BA and PA bind through the carboxyl groups to the MgO (100) surface. Upon adsorption at 100 K BA binds in an asymmetric bidentate geometry which exhibits a small tilting angle between the aromatic plane and the surface. Beyond the monolayer, a disordered multilayer film grows, which crystallizes under formation of dimers at around 180 K as indicated by a characteristic splitting of the IR bands. The BA multilayer desorbs at 240 K. Upon adsorption at 300 K, only a BA monolayer forms. Again, BA forms an asymmetric bidentate but with a larger tilting angle compared to low-temperature adsorption. For PA adsorption at 100 K, the adsorption mechanism is observed to change with coverage. At low coverage, both carboxyl groups are deprotonated, and the molecule forms an asymmetric bis-bidentate carboxylate with the aromatic plane nearly perpendicular to the surface. At high coverage, only one carboxyl group binds to the surface and forms an asymmetric bidentate carboxylate while the molecules maintain an upright standing orientation. During PVD of PA, a small fraction of phthalic anhydride (PAA) is formed which coadsorbs at low temperature. Upon annealing, the PAA. desorbs around 250 K, triggering a structural transformation of the PA multilayer during which the PA adopts a more flat lying orientation. The PA multilayer itself desorbs around 310 K. Therefore, only monolayer of PA is stable around 300 K. Again, the adsorption mechanism is coverage dependent, changing from a bis-bidentate carboxylate at lower coverage to a monobidentate carboxylate at higher coverage.

Dehydrogenation mechanism of liquid organic hydrogen carriers: Dodecahydro-N-ethylcarbazole on Pd(111) - Amende, Maximilian; Schernich, Stefan; Sobota, Marek; Nikiforidis, Ioannis; Hieringer, Wolfgang; Assenbaum, Daniel; Gleichweit, Christoph; Drescher, Hans-Jörg; Papp, Christian; Steinrück, Hans-Peter; Görling, Andreas; Wasserscheid, Peter; et al. (Chemistry - A European Journal, 2013)
Dodecahydro-N-ethylcarbazole (H-NEC) has been proposed as a potential liquid organic hydrogen carrier (LOHC) for chemical energy storage, as it combines both favourable physicochemical and thermodynamic properties. The design of optimised dehydrogenation catalysts for LOHC technology requires a detailed understanding of the reaction pathways and the microkinetics. Here, we investigate the dehydrogenation mechanism of H-NEC on Pd(111) by using a surface-science approach under ultrahigh vacuum conditions. By combining infrared reflection-absorption spectroscopy, density functional theory calculations and X-ray photoelectron spectroscopy, surface intermediates and their stability are identified. We show that H-NEC adsorbs molecularly up to 173 K. Above this temperature (223 K), activation of C-H bonds is observed within the five-membered ring. Rapid dehydrogenation occurs to octahydro-N-ethylcarbazole (H-NEC), which is identified as a stable surface intermediate at 223 K. Above 273 K, further dehydrogenation of H -NEC proceeds within the six-membered rings. Starting from clean Pd(111), C-N bond scission, an undesired side reaction, is observed above 350 K. By complementing surface spectroscopy, we present a temperature-programmed molecular beam experiment, which permits direct observation of dehydrogenation products in the gas phase during continuous dosing of the LOHC. We identify H-NEC as the main product desorbing from Pd(111). The onset temperature for H-NEC desorption is 330 K, the maximum reaction rate is reached around 550 K. The fact that preferential desorption of H -NEC is observed even above the temperature threshold for H -NEC dehydrogenation on the clean surface is attributed to the presence of surface dehydrogenation and decomposition products during continuous reactant exposure. © 2013 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.

Dehydrogenation of Dodecahydro-N-ethylcarbazole on Pd/Al2O3 Model Catalysts - Sobota, Marek; Nikiforidis, Ioannis; Amende, Maximilian; Sanmartίn Zanón, Beatriz; Staudt, Thorsten; Höfert, Oliver; Lykhach, Yaroslava; Papp, Christian; Hieringer, Wolfgang; Laurin, Mathias; Assenbaum, Daniel; Wasserscheid, Peter; et al. (Chemistry - A European Journal, 2011)
To elucidate the dehydrogenation mechanism of dodecahydro-N-ethylcarbazole (H-12-NEC) on supported Pd catalysts, we have performed a model study under ultra high vacuum (UHV) conditions. H-12-NEC and its final dehydrogenation product, N-ethylcarbazole (NEC), were deposited by physical vapor deposition (PVD) at temperatures between 120 K and 520 K onto a supported model catalyst, which consisted of Pd nanoparticles grown on a well-ordered alumina film on NiAl(110). Adsorption and thermally induced surface reactions were followed by infrared reflection absorption spectroscopy (IRAS) and high-resolution X-ray photoelectron spectroscopy (HR-XPS) in combination with density functional theory (DFT) calculations. It was shown that, at 120 K, H-12-NEC adsorbs molecularly both on the Al2O3/NiAl(110) support and on the Pd particles. Initial activation of the molecule occurs through C-H bond scission at the 8a- and 9a-positions of the carbazole skeleton at temperatures above 170 K. Dehydrogenation successively proceeds with increasing temperature. Around 350 K, breakage of one C-N bond occurs accompanied by further dehydrogenation of the carbon skeleton. The decomposition intermediates reside on the surface up to 500 K. At higher temperatures, further decay to small fragments and atomic species is observed. These species block most of the absorption sites on the Pd particles, but can be oxidatively removed by heating in oxygen at 600 K, fully restoring the original adsorption properties of the model catalyst.
Keywords: density functional calculations; IR spectroscopy; liquid organic hydrogen carriers; photo-electron spectroscopy; supported catalysts

Dehydrogenation of dodecahydro-N-ethylcarbazole on Pt(111) - Gleichweit, Christoph; Amende, Maximilian; Schernich, Stefan; Zhao, Wei; Lorenz, Michael Peter Andreas; Höfert, Oliver; Brückner, Nicole; Wasserscheid, Peter; Libuda, Jörg; Steinrück, Hans-Peter; Papp, Christian (Chemsuschem, 2013)
Sloshing hydrogen: Liquid organic hydrogen carriers are high-boiling organic molecules, which can be reversibly hydrogenated and dehydrogenated in catalytic processes and are, therefore, a promising chemical hydrogen storage material. One of the promising candidates is the pair N-ethylcarbazole/perhydro- N-ethylcarbazole (NEC/H-NEC). The dehydrogenation and possible side reactions on a Pt(111) surface are evaluated in unprecedented detail. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Dicyclohexylmethane as a Liquid Organic Hydrogen Carrier: A Model Study on the Dehydrogenation Mechanism over Pd(111) - Amende, Maximilian; Gleichweit, Christoph; Xu, Tao; Höfert, Oliver; Koch, Marcus; Wasserscheid, Peter; Steinrück, Hans-Peter; Papp, Christian; Libuda, Jörg (Catalysis Letters, 2016)
Abstract: We have studied the dehydrogenation of the liquid organic hydrogen carrier (LOHC) dicyclohexylmethane (DCHM) to diphenylmethane (DPM) and its side reactions on a Pd(111) single crystal surface. The adsorption and thermal evolution of both DPM and DCHM was measured in situ in ultrahigh vacuum (UHV) using synchrotron radiation-based high-resolution X-ray photoelectron spectroscopy (HR-XPS). We found that after deposition at 170 K, the hydrogen-lean DPM undergoes C-H bond scission at the methylene bridge at 200 K and, starting at 360 K, complete dehydrogenation of the phenyl rings occurs. Above 600 K, atomic carbon incorporates into the Pd bulk. For the hydrogen-rich DCHM, the first stable dehydrogenation intermediate, a double π-allylic species, forms already at 190 K. Until 340 K, further dehydrogenation of the phenyl rings and of the methylene bridge occurs, yielding the same intermediate that is formed upon heating of DPM to this temperature, that is, DPM dehydrogenated at the methylene bridge. The onset for the complete dehydrogenation of this intermediate occurs at a much higher temperature than after adsorption of DPM. This behavior is mainly attributed to coadsorbed hydrogen from DCHM dehydrogenation. The results are discussed in comparison to our previous study of DPM and DCHM on Pt(111) revealing strong material dependencies. Graphical Abstract: [Figure not available: see fulltext.]
Keywords: Liquid organic hydrogen carrier; Model catalysis; X-ray photoelectron spectroscopy

Functionalized Porphyrins on an Atomically Defined Oxide Surface: Anchoring and Coverage-Dependent Reorientation of MCTPP on Co3O4(111) - Werner, Kristin; Mohr, Susanne; Schwarz, Matthias; Xu, Tao; Amende, Maximilian; Döpper, Tibor; Görling, Andreas; Libuda, Jörg (Journal of Physical Chemistry Letters, 2016)
We have studied the adsorption of tetraphenylporphyrin (2HTPP) and its carboxylated counterpart mono-para-carboxyphenyltriphenylporphyrin (MCTPP) on an atomically defined CoO(111) film under ultrahigh vacuum (UHV) conditions. Using time-resolved infrared reflection absorption spectroscopy (TR-IRAS), we show that 2HTPP adsorbs molecularly in a flat-lying orientation, whereas MCTPP binds to the surface via formation of a chelating bidentate carboxylate upon deposition at 400 K. Combining TR-IRAS and density-functional theory (DFT), we determine the molecular tilting angle as a function of coverage. We show that the MCTPP adsorption geometry changes from a nearly flat-lying orientation (tilting angle <30°) at low coverage to a nearly perfectly upright-standing orientation (tilting angle of approximately 80°) in the full monolayer.

Ionic liquid based model catalysis: Interaction of [BMIM][Tf2N] with Pd nanoparticles supported on an ordered alumina film - Sobota, Marek; Schmid, Martin; Happel, Markus; Amende, Maximilian; Maier, Florian; Steinrück, Hans-Peter; Paape, Natalia; Wasserscheid, Peter; Laurin, Mathias; Gottfried, Michael; Libuda, Jörg (Physical Chemistry Chemical Physics, 2010)
Towards a better understanding of novel catalytic materials consisting of supported noble metal catalysts modified by an ionic liquid (IL) film, we have performed a study under ultrahigh-vacuum (UHV) conditions. The model surface consists of Pd nanoparticles grown in UHV on an ordered alumina film on NiAl(110). Thin films of the room temperature IL 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide [BMIM][TfN] are deposited onto this surface by means of physical vapor deposition (PVD). The interaction of the IL with clean and CO-covered Pd/AlO/NiAl(110) at 300 K and the thermal behavior of the deposited IL films on Pd/AlO /NiAl(110) are investigated by time-resolved infrared reflection absorption spectroscopy (TR-IRAS) and X-ray photoelectron spectroscopy (XPS). At 300 K, the IL adsorbs molecularly both onto the Pd particles and onto the alumina. The IR spectra suggest that the [TfN] anions interact with Pd sites preferentially via the sulfonyl groups. CO pre-adsorbed on the Pd particles is partially displaced by the IL, even at 300 K, and only the part of CO adsorbed onto hollow sites on (111) facets of the Pd particles remains in place. Upon heating to temperatures higher than the desorption temperature of the IL (>400 K), molecular desorption of the IL competes with decomposition. The decomposition products, atomic species and small fragments, remain preferentially adsorbed onto the Pd nanoparticles and strongly modify their surface properties. Most of the decomposition products originate from the [BMIM] cations, whereas the [TfN] anions desorb for the most part. © 2010 the Owner Societies.

Keeping argon under a graphene lid - Argon intercalation between graphene and nickel(111) - Steinrück, Hans-Peter; Bauer, Udo; Gotterbarm, Karin; Späth, Florian; Papp, Christian; Höfert, Oliver; Gleichweit, Christoph; Amende, Maximilian (Surface Science, 2016)
We report on the intercalation of graphene grown on a Ni(111) crystal with argon. Argon is implanted in the Ni(111) crystal by ion bombardment before graphene growth, and diffuses to the surface during the growth of graphene at elevated temperatures. Graphene acts as an atomically thin barrier and keeps the argon underneath. We investigated this system with high resolution X-ray photoelectron spectroscopy. From our experiments we determined the mean quantities of argon under graphene. From our analysis, a simple model to determine the pressure under the graphene layer is presented. In our measurements, we find an increased thermal stability of the intercalated graphene as compared to non-intercalated graphene on Ni(111).
Keywords: Graphene; Intercalation; Nickel; XPS

Ligand Effects in SCILL Model Systems: Site-Specific Interactions with Pt and Pd Nanoparticles - Sobota, Marek; Happel, Markus; Amende, Maximilian; Paape, Natalia; Wasserscheid, Peter; Laurin, Mathias; Libuda, Jörg (Advanced Materials, 2011)
Ionic liquids (ILs), such as [BMIM][Tf_2N], on well-defined SCILL model catalysts are able to replace weakly adsorbed CO. On Pt, on-top CO remains adsorbed under the ionic liquid layer, but its IR signal red-shifts by over 30 cm-1. IL–adsorbate interactions are mediated by the noble metal and similar to ligands.

Model catalytic studies of liquid organic hydrogen carriers: Dehydrogenation and decomposition mechanisms of dodecahydro-n-ethylcarbazole on pt(111) - Amende, Maximilian; Gleichweit, Christoph; Werner, Kristin; Schernich, Stefan; Zhao, Wei; Lorenz, Michael Peter Andreas; Höfert, Oliver; Papp, Christian; Koch, Marcus; Wasserscheid, Peter; Laurin, Mathias; Steinrück, Hans-Peter; et al. (ACS Catalysis, 2014)
Liquid organic hydrogen carriers (LOHC) are compounds that enable chemical energy storage through reversible hydrogenation. They are considered a promising technology to decouple energy production and consumption by combining high-energy densities with easy handling. A prominent LOHC is N-ethylcarbazole (NEC), which is reversibly hydrogenated to dodecahydro-N-ethylcarbazole (H -NEC). We studied the reaction of H-NEC on Pt(111) under ultrahigh vacuum (UHV) conditions by applying infrared reflection-absorption spectroscopy, synchrotron radiation-based high resolution X-ray photoelectron spectroscopy, and temperature-programmed molecular beam methods. We show that molecular adsorption of H-NEC on Pt(111) occurs at temperatures between 173 and 223 K, followed by initial C-H bond activation in direct proximity to the N atom. As the first stable dehydrogenation product, we identify octahydro-N-ethylcarbazole (H -NEC). Dehydrogenation to H-NEC occurs slowly between 223 and 273 K and much faster above 273 K. Stepwise dehydrogenation to NEC proceeds while heating to 380 K. An undesired side reaction, C-N bond scission, was observed above 390 K. H-NEC and H-carbazole are the dominant products desorbing from the surface. Desorption occurs at higher temperatures than H-NEC formation. We show that desorption and dehydrogenation activity are directly linked to the number of adsorption sites being blocked by reaction intermediates. © 2014 American Chemical Society.

Preparation and Adsorption Properties of Pd Nanoparticles Supported on TiO2 Nanotubes - Honciuc, Andrei; Laurin, Mathias; Albu, Sergiu; Amende, Maximilian; Sobota, Marek; Lynch, Robert; Schmuki, Patrik; Libuda, Jörg (Journal of Physical Chemistry C, 2010)
Here we present preparation methods for a series of novel model heterogeneous catalysts consisting of Pd nanoparticles dispersed on self-organized TiO2 nanotube arrays (TiNTs). For a comprehensive comparative study of TiNTs' surface adsorption properties, different chemical and physical methods were employed for the deposition of the Pd nanoparticles: (i) e-beam deposition in high vacuum (HV) and (ii) in ultrahigh vacuum (UHV), (iii) impregnation, and (iv) metal precipitation. Following preparation, the Pd/TiNTs were exposed to several O-2 (oxidative) and CO (reductive) cleaning cycles at 500 K in UHV. After each cleaning cycle, the CO adsorption properties were systematically probed with time-resolved infrared reflection-adsorption spectroscopy to monitor the surface state of the catalyst. It is shown that clean and well-defined Pd/TiNT catalysts can be obtained, which are well suited for future adsorption and reactivity studies.

Regeneration of LOHC dehydrogenation catalysts: In-situ IR spectroscopy on single crystals, model catalysts, and real catalysts from UHV to near ambient pressure - Amende, Maximilian; Kaftan, Andre; Bachmann, Philipp; Brehmer, Richard; Preuster, Patrick; Koch, Marcus; Wasserscheid, Peter; Libuda, Jörg (Applied Surface Science, 2016)
The Liquid Organic Hydrogen Carrier (LOHC) concept offers an efficient route to store hydrogen using organic compounds that are reversibly hydrogenated and dehydrogenated. One important challenge towards application of the LOHC technology at a larger scale is to minimize degradation of Pt-based dehydrogenation catalysts during long-term operation. Herein, we investigate the regeneration of Pt/alumina catalysts poisoned by LOHC degradation. We combine ultrahigh vacuum (UHV) studies on Pt(111), investigations on well-defined Pt/AlO model catalysts, and near-ambient pressure (NAP) measurements on real core-shell Pt/AlO catalyst pellets. The catalysts were purposely poisoned by reaction with the LOHC perhydro-dibenzyltoluene (H18-MSH) and with dicyclohexylmethane (DCHM) as a simpler model compound. We focus on oxidative regeneration under conditions that may be applied in real dehydrogenation reactors. The degree of poisoning and regeneration under oxidative reaction conditions was quantified using CO as a probe molecule and measured by infrared reflection-absorption spectroscopy (IRAS) and diffuse reflectance Fourier transform IR spectroscopy (DRIFTS) for planar model systems and real catalysts, respectively. We find that regeneration strongly depends on the composition of the catalyst surface. While the clean surface of a poisoned Pt(111) single crystal is fully restored upon thermal treatment in oxygen up to 700 K, contaminated Pt/AlO model catalyst and core-shell pellet were only partially restored under the applied reaction conditions. Whereas partial regeneration on facet-like sites on supported catalysts is more facile than on Pt(111), carbonaceous deposits adsorbed at low-coordinated defect sites impede full regeneration of the Pt/AlO catalysts.
Keywords: Infrared spectroscopy; Liquid Organic Hydrogen Carrier; Materials gap; Model catalysis; Pressure gap; Real catalysis

Size and structure effects controlling the stability of the liquid organic hydrogen carrier dodecahydro- N -ethylcarbazole during dehydrogenation over pt model catalysts - Amende, Maximilian; Gleichweit, Christoph; Schernich, Stefan; Höfert, Oliver; Lorenz, Michael Peter Andreas; Zhao, Wei; Koch, Marcus; Obesser, Katharina; Papp, Christian; Wasserscheid, Peter; Steinrück, Hans-Peter; Libuda, Jörg (Journal of Physical Chemistry Letters, 2014)
Hydrogen can be stored conveniently using so-called liquid organic hydrogen carriers (LOHCs), for example, N-ethylcarbazole (NEC), which can be reversibly hydrogenated to dodecahydro-N-ethylcarbazole (H-NEC). In this study, we focus on the dealkylation of H-NEC, an undesired side reaction, which competes with dehydrogenation. The structural sensivity of dealkylation was studied by high-resolution X-ray photoelectron spectroscopy (HR-XPS) on AlO-supported Pt model catalysts and Pt(111) single crystals. We show that the morphology of the Pt deposit strongly influences LOHC degradation via C-N bond breakage. On smaller, defect-rich Pt particles, the onset of dealkylation is shifted by 90 K to lower temperatures as compared to large, well-shaped particles and well-ordered Pt(111). We attribute these effects to a reduced activation barrier for C-N bond breakage at low-coordinated Pt sites, which are abundant on small Pt aggregates but are rare on large particles and single crystal surfaces. © 2014 American Chemical Society.

Structure-Dependent Anchoring of Organic Molecules to Atomically Defined Oxide Surfaces: Phthalic Acid on Co3O4(111), CoO(100), and CoO(111) - Xu, Tao; Schwarz, Matthias; Werner, Kristin; Mohr, Susanne; Amende, Maximilian; Libuda, Jörg (Chemistry - A European Journal, 2016)
We have performed a model study to explore the influence of surface structure on the anchoring of organic molecules on oxide materials. Specifically, we have investigated the adsorption of phthalic acid (PA) on three different, well-ordered, and atomically defined cobalt oxide surfaces, namely 1)Co3O4(111), 2)CoO(111), and 3)CoO(100) on Ir(100). PA was deposited by physical vapor deposition (PVD). The formation of the PA films and interfacial reactions were monitored in situ during growth by isothermal time-resolved IR reflection absorption spectroscopy (TR-IRAS) under ultrahigh vacuum (UHV) conditions. We observed a pronounced structure dependence on the three surfaces with three distinctively different binding geometries and characteristic differences depending on the temperature and coverage. 1)PA initially binds to Co3O4(111) through the formation of a chelating bis-carboxylate with the molecular plane oriented perpendicularly to the surface. Similar species were observed both at low temperature (130K) and at room temperature (300K). With increasing exposure, chelating mono-carboxylates became more abundant and partially replaced the bis-carboxylate. 2)PA binds to CoO(100) in the form of a bridging bis-carboxylate for low coverage. Upon prolonged deposition of PA at low temperature, the bis-carboxylates were converted into mono-carboxylate species. In contrast, the bis-carboxylate layer was very stable at 300K. 3)For CoO(111) we observed a temperature-dependent change in the adsorption mechanism. Although PA binds as a mono-carboxylate in a bridging bidentate fashion at low temperature (130K), a strongly distorted bis-carboxylate was formed at 300K, possibly as a result of temperature-dependent restructuring of the surface. The results show that the adsorption geometry of PA depends on the atomic structure of the oxide surface. The structure dependence can be rationalized by the different arrangements of cobalt ions at the three surfaces.
Keywords: adsorption; carboxylic acids; cobalt; IR spectroscopy; thin films

Surface Reactions of Dicyclohexylmethane on Pt(111) - Gleichweit, Christoph; Amende, Maximilian; Höfert, Oliver; Xu, Tao; Späth, Florian; Brückner, Nicole; Wasserscheid, Peter; Libuda, Jörg; Steinrück, Hans-Peter; Papp, Christian (Journal of Physical Chemistry C, 2015)
We investigated the surface reaction of the liquid organic hydrogen carrier dicydohexylmethane (DCHM) on Pt(111) in ultrahigh vacuum by high-resolution X-ray photoelectron spectroscopy, temperature-programmed desorption, near-edge X-ray absorption fine structure, and infrared reflection absorption spectroscopy. Additionally, the hydrogen-lean molecule diphenylmethane and the relevant molecular fragments of DCHM, methylcyclohexane, and toluene were studied to elucidate the reaction steps of DCHM. We find dehydrogenation of DCHM in the range of 200-260 K, to form a double-sided pi-allylic species coadsorbed with hydrogen. Subsequently, similar to 30% of the molecules desorb, and for similar to 70%, one of the pi-allyls reacts to a phenyl group between 260 and 330 K, accompanied by associative hydrogen desorption. Above 360 K, the second pi-allylic species is dehydrogenated to a phenyl ring. This is accompanied by C-H bond scission at the methylene group, which is an unwanted decomposition step in the hydrogen storage cycle, as it alters the original hydrogen carrier DCHM. Above 450 K, we find further decomposition steps which we assign to C-H abstraction at the phenyl rings.

The surface structure matters: thermal stability of phthalic acid anchored to atomically-defined cobalt oxide films - Xu, Tao; Schwarz, Matthias; Werner, Kristin; Mohr, Susanne; Amende, Maximilian; Libuda, Jörg (Physical Chemistry Chemical Physics, 2016)
We have investigated the influence of the structure of oxide surfaces on the thermal stability of anchored phthalic acid (PA) thin films. Specifically, we have performed temperature programmed infrared reflection absorption spectroscopy (TP-IRAS) of PA films deposited by physical vapor deposition (PVD) in ultra-high vacuum (UVH) onto three well-ordered surfaces: Co3O4(111), CoO(111) and CoO(100), all grown on Ir(100). Restructuring and desorption of PA were monitored in situ by TP-IRAS. Upon annealing of PA multilayers, co-adsorbed phthalic anhydride (PAA) desorbs at 200 K and a structural transition to a flat-lying adsorption geometry occurs at 250 K, before the PA multilayer desorbs at 300 K. At temperatures up to 400 K co-adsorbed mono-carboxylates partially desorb and partially convert to bis-carboxylates. Pronounced structure dependencies are observed regarding the thermal stability of the anchored bis-carboxylate monolayers. From Co3O4(111) the anchored PA desorbs over a wide range of temperatures centered at around 540 K. Weaker binding is observed for CoO(111) with desorption temperatures centered around 490 K. The strongest binding occurs on CoO(100), where the anchored PA films are found to be perfectly stable up to 510 K, before desorption starts and centers at around 580 K. The differences in binding strength are rationalized based on the density and the accessibility of the surface Co2+ ions. The findings show that the atomic structure of the oxide surface plays an important role in the stability of organic hybrid interfaces.